Pengaruh Likuiditas, Profitabilitas, Dan Leverage Terhadap Harga Saham (Studi Empiris Pada Perusahaan Sub-Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020) - Ismi Fajriati; M. Wahyudin Zarkasyi (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This research aims to identify and examine the relationship between liquidity, profitability, and leverage with stock prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2016-2020. Determination of the sample using purposive sampling method using a total of 11 companies as observation data. Multiple linear regression analysis was used as the method of analysis. The results of the research show that liquidity proxied by Current Ratio does not have a partial effect on Stock Prices, Profitability proxied by Return on Assets has a partial influence on Stock Prices, Leverage proxied by Debt to Equity has a partial influence on Stock Prices, and Effect of Liquidity, Profitability, and Leverage Simultaneously affect the Stock Price Keywords: Liquidity, Profitability, Leverage, Stock , Food and Beverage Sub-sector Companies